Genetic diversity in nutritional composition of oat (Avena sativa L.) germplasm reported from Pakistan - Ihsan, Mohammad; Nisar, Mohammad; Nazir, Nausheen; Zahoor, Muhammad; Khalil, Atif Ali Khan; Ghafoor, Abdul; Khan, Arshad; Mothana, Ramzi A.; Ullah, Riaz; Ahmad, Nisar (Saudi journal of biological sciences, 2022)
In the present study, 30 potential germplasm of oat (Avena sativa L.) were subjected to proximate, elemental, and HPLC analysis to provide a scientific basis to genetic diversity present among them. The extracts of the selected germplasms were also evaluated for their antioxidant potentials through DPPH and ABTS assays. Proximate analysis showed protein contents to be in the range 8.35-17.72% with the highest protein contents in the accession line 22,365 (17.72 ± 0.38%). The genotype-725 showed the highest carbohydrate, and dry matter (53.35 ± 0.01 and 93.50 ± 0.07% respectively) contents whereas, the germplasm-830 contained the highest fat (7.88 ± 0.12%) contents while the highest moisture contents were there in germplasm-22348 (11.95 ± 0.06%). The crude fiber contents (19.67 ± 0.19%) were found high in germplasm-832. The mentioned contents were also correlated to each other where a negative (−0.431*) correlation was noted for crude protein and carbohydrate while ash content to crude protein has a positive (0.38*) correlation. A positive and a negative correlation were there in Crude fats/crude protein (0.30*) and crude fats/moisture contents (−0.39*) respectively. Principal component analysis showed an Eigenvalue of 0.76 with a total variation of 85.01% when applied to proximate components. Based on cluster analysis to proximate composition all the oat germplasms were divided into 5 sub-clusters, where accession numbers 769 and 817 were found to be the most diverse genotypes. The elemental analysis confirmed the presence of magnesium (2.89-7.62 mg/L), sodium (3.71-8.03 mg/L), manganese (0.93-3.71 mg/L), copper (0.35-3.36 mg/L), iron (2.15-6.82 mg/L), zinc (1.30-3.37 mg/L), chromium (0.37-3.34 mg/L), and potassium (50.70-59.60 mg/L) in the selected germplasms. Principal component analysis for elemental composition showed the total variation of 73.75% with the Eigenvalue of 0.97. Cluster analysis on an elemental basis divided all the oat germplasms into 7 sub-clusters where accession numbers 769 and 22,350 were found to be the most diverse germplasm. Phytochemical analysis performed through HPLC resulted in the identification of nine possible compounds (malic acid, epigallocatechin gallate, quercetin, morin, ellagic acid, catechin hydrate, rutin, pyrogallol, and mandelic acid) in various germplasm of oat. A concentration-dependent antioxidant response was recorded when extracts were tested as an inhibitor of DPPH and ABTS free radicals. The results revealed that oat grains are a good source of nutrients, minerals, and phytochemicals that can be used as nutraceuticals and as food. The genetic differences revealed that this plant can be grown under varied environmental conditions.